Calibration of the simulation parameters of the particulate materials in film mixed materials - Liang, Rongqing; Chen, Xuegeng; Jiang, Peng; Zhang, Bingcheng; Meng, Hewei; Peng, Xiangbin; Kan, Za (International Journal of Agricultural and Biological Engineering, 2020)
In order to obtain accurate contact parameters of a particulate material in residual film mixture collected by cotton field machine in Xinjiang, the angle of repose test and inclined plane test were carried out. In the tests, the angles of repose of the particulate material with the water content of (6.26±1.5)% and (14.1±2.1)% were measured respectively, as well as the static sliding friction angle between the particulate material and the residual film. At the same time, the EDEM software was used to calibrate the coefficient of restitution, static friction coefficient and dynamic friction coefficient between the material and the film. Then, the second-order response model between contact parameters and the angle of repose and static sliding friction angle was constructed. In addition, the optimal contact parameters between the granular materials and the mulch were obtained by fitting the physical test data. The results indicated that the errors between the physical test results and the numerical simulation results are small. It was proved that the second-order response model could predict the repose angle of granular materials and the static sliding friction angle between granular materials and farmland film. This study could provide theoretical support for the subsequent model construction of the residual film mixture collected by the cotton field machine.Keywords: cotton field, agricultural film, particulate material, EDEM, contact parameter, response model, calibrationDOI: 10.25165/j.ijabe.20201304.5586Citation: Liang R Q, Chen X G, Jiang P, Zhang B C, Meng H W, Peng X B, et al. Calibration of the simulation parameters of the particulate materials in film mixed materials. Int J Agric & Biol Eng, 2020; 13(4): 29–36.